Gendered Harms in Armed Conflict: International Legal Responses to the Gendered Effects of the War in Sudan - Dams, Naima (AUC Knowledge Fountain, 2026)
This thesis interrogates how international law conceptualizes, prosecutes, and ultimately limits the understanding of sexual violence in contexts of war and displacement. Drawing on feminist legal theory, postcolonial critique, and ethnographic fieldwork with Sudanese women displaced in Egypt, it questions the dominant legal framing of conflict-related sexual violence (CRSV) as episodic, exceptional, and individualized. Instead, it reveals sexual violence as structural, continuous, and embedded in the everyday realities of racialized, gendered, and colonial harm. Through ethnographical narratives, the study exposes how survivors' experiences often exceed the legibility frameworks of humanitarian and legal institutions, which prioritize spectacular, forensic evidence over slow, atmospheric, or “ordinary” forms of violence. It critiques international law's reliance on individualized liability, including direct perpetration, forensic verification, and intent, as well as its failure to account for collective, institutional, and infrastructural forms of complicity. By engaging critically with different doctrines of international law, the thesis demonstrates how international legal mechanisms obscure the cultural, militarized, and bureaucratic conditions that normalize sexual violence. Ultimately, the thesis offers a critical reflection on justice, one that centers recognition, ethical responsibility, and structural transformation. It advocates for a feminist legal praxis that listens beyond what the law can codify, values narrative, and prioritizes survivors’ lived knowledge over carceral performance.